2021
DOI: 10.3390/ph14060492
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Oxide Nanoparticles Protected with Terpenoids as a Substance in Redox Imbalance Normalization in Burns

Abstract: Preliminary protection of zinc oxide nanoparticles (ZnO NPs) with terpenoids such as betulin, its derivatives, and essential oils components has been proposed to produce gel-like oleophilic and hydrophilic formulations. We studied the properties of gel-like dispersions of ZnO NPs with immobilized terpenoids and their effects on the activity of LDH, GR, G6PDH, restoration of redox balance of co-enzyme pairs NAD+/NADH and NADP+/NADPH, as well as the activity of SOD, catalase, AlDH in erythrocytes in the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The substantial effect of the TLRs signaling pathway activation on cardiomyocytes remains controversial. 38 42 We primarily hypothesized TLR4 signaling was activated by NETs and led to the apoptosis of cardiomyocytes. However, the knockdown of TLR4 resulted in increased NETs-mediated cardiomyocyte death, which demonstrated the protective role of TLR4 in the process (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The substantial effect of the TLRs signaling pathway activation on cardiomyocytes remains controversial. 38 42 We primarily hypothesized TLR4 signaling was activated by NETs and led to the apoptosis of cardiomyocytes. However, the knockdown of TLR4 resulted in increased NETs-mediated cardiomyocyte death, which demonstrated the protective role of TLR4 in the process (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Inorganic nanoparticles are biocompatible, protect bioactive from degradation, with a size that can vary according to the core material used (MOHAMMADPOUR et al, 2019). Metallic and semiconductor nanoparticles such as iron oxide (ANGHEL et al, 2013), cobalt (HOU et al, 2020 and zinc oxide (MELNIKOVA et al, 2021) were used incorporating essential oils to assess healing potential.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…Regarding the essential oils evaluated, lavender, eucalyptus and clove were the ones that most had their properties analyzed, in concentrations ranging from 1-5%. Regarding the in vivo forms of administration, the topical route was used (MELNIKOVA et al, 2021;HOU et al, 2020;KHAN et al, 2021;HAJIALI et al, 2015;KALITA et al, 2017;KHEZRI;FARAHPOUR;RAD, 2019;SAPORITO et al, 2018;KAMEL et al, 2022;RIZG et al, 2022;LI et al, 2021;SUGUMAR et al, 2014) and oral (SHAKEEL et al , 2019;ALAM et al, 2017;ALAM et al, 2018).…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, in an experiment on rats, we showed that betulin diphosphate is a promising API for treating burns as a component of wound dressings made of bacterial cellulose and zinc oxide nanoparticles, and various dispersions, including oleogels with vegetable oils [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%